Bilateral Atypical Femoral Fractures in a Patient with Multiple Myeloma Treated with Intravenous Bisphosphonate Therapy. (22nd July 2014) - Tonogai, Ichiro; Goto, Tomohiro; Hamada, Daisuke; Iwame, Toshiyuki; Yoshioka, Shinji; Tsutsui, Takahiko; Goda, Yuichiro; Egawa, Hiroshi; Sairyo, Koichi
Abstract : Bisphosphonates are currently the standard approach to managing bone disease in multiple myeloma. Bisphosphonates have high bone affinity that inhibits osteoclastic activity and additionally reduces the growth factors released from malignant or osteoblastic cells, thereby impairing abnormal bone remodeling which leads to osteolysis. However, patients of multiple myeloma may be at a higher risk of atypical femoral fractures because the treatment for malignant myeloma requires notably higher cumulative doses of bisphosphonates. Here we present a patient with bilateral atypical femoral fractures and multiple myeloma treated with intravenous bisphosphonate therapy.